The Uji Aktivitas Antibakteri Ekstrak Metanol dan Etil Asetat pada Benalu Kakao (Dendrophthoe Pentandra (L.) Miq) terhadap Bakteri Staphylococcus Aureus dan Escherichia Coli - Diningsih, Ayus; Aswan, Yulinda (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Research on the test of the antibacterial activity of methanol and ethyl acetate extracts on cocoa parasites (dendrophthoe pentandra (l.) Miq.) on staphylococcus aureus and escherichia coli bacteria was carried out. The purpose of this research was to determine the antibacterial activity of cacao parasite (Dendrophthoe pentandra (L.) Miq.) Leaves against Staphylococcus aureus and Escherichia coli bacteria. This research is a laboratory by testing the anti-bacterial activity of cocoa parasite samples (Dendrophthoe pentandra (L.) Miq). The results of the study stated that the antibacterial of methanol and ethyl acetate extract of cocoa parasite leaves was able to inhibit the growth of Staphylococcus aureus and Escherichia coli bacteria around disc paper after being diluted in DMSO with variations in the concentration of methanol extract and ethyl acetate of cocoa parasite leaves, namely methanol extract of cocoa parasite leaves on gram bacteria, after being diluted in DMSO with variations in the concentration of methanol and ethyl acetate extracts of cocoa positive Staphylococcus aureus with a concentration of 500 mg / ml showed activity with inhibition zones 13.9 mm (weak / resistant), in gram negative bacteria Escherichia coli with a concentration of 500 mg / ml showed activity with inhibition zones of 13.8 mm each (weak) / resistant). Ethyl acetate extract of cocoa parasite leaves in gram-positive bacteria Staphylococcus aureus with a concentration of 500 mg / ml showed activity with inhibition zones 16.2 mm (moderate / intermediate) and in gram-negative bacteria Escherichia coli with concentrations of 500 mg / ml showed activity with inhibition zones 15.1 mm (moderate / intermediate).